Dehydration of 2‐Octanol over Ca‐doped CeO2 Catalysts. Issue 3 (3rd January 2017) - Gnanamani, Muthu Kumaran; Jacobs, Gary; Shafer, Wilson D.; Davis, Burtron H.
Abstract: Vapor‐phase catalytic dehydration of 2‐octanol was investigated over Ca‐doped CeO2 at 375 °C and atmospheric pressure. Ca doping up to 0.15 wt % was found to increase the dehydration activity for 2‐octanol, whereas further increases in Ca content (0.50 and 1.25 wt %) detrimentally affected the conversion. Catalyst surface area and pore volume increased with increasing Ca content in Ca‐doped CeO2 . Hydrogen temperature‐programmed reduction (TPR) profiles indicate that the partially reduced state of surface ceria (i.e., Ce 3+ ), which increases with increasing Ca loading up to 0.15 wt %, might play an important role in promoting dehydration. Abstract : Doping for dehydration : The dehydration of 2‐octanol catalyzed by undoped and Ca‐doped CeO2 was investigated. The dehydration activity for 2‐octanol was found to increase with increasing Ca content in CeO2 up to 0.5 wt %; however, the selectivity of the catalyst did not change.